Multiple Sclerosis - Jamil, Shahid; Noor, Irshad; Khan, Parvez; Rehman, Masood Ur (Journal of Postgraduate Medical Institute, 2011)
Multiple sclerosis is perhaps not rare in N.W.F.P. Here are case reports of two patients, recently admitted in our unit at the Postgraduate Medical Institutel, Lady Reading Hospital, Peshawar, within a space of three months. Case -1 . A 26 years old woman was admitted with the complaints of weakness in all four limbs and diminution of vision for one month. The weakness started in her left lower limb, later affecting the right lower limb as well. After about a week, the upper limbs were involved first left and then the right side. She also had back pain of aching character which was aggravatged by movements. Three years ago she was admitted for paraplegia with sensory loss upto the umbilicus. she made gradual but complete recovery. Case -2 . A 21 year old girl was admitted with the complaints of inability to walk for twenty days. She had inconitnence of urine and had attacks of severe bilateral facial pain. She was admitted and investigated for paraplegia seven years ago. No cause was found, and was sent home on steroids. There was subjective improvement and she became mobile. She had gradual deterioration of vision in her lefte eye and now her right eye was painful with diminished vision. On examination she was febrile 102 F , asthenic, conscious oriented in time and space. She had no evident spinal lesion.